Essential practical NMR for organic chemistry - Richards, S. A.; Hollerton, J. C. [ (John C.)] , 1959- (John Wiley & Sons, 2010)
This book describes the use of NMR spectroscopy for dealing with problems of small organic molecule structural elucidation